Feminism and linguistic theory - Cameron, Deborah (Macmillan, 1992)
An introduction to theories about language in attempts to understand and transform women's lives. This evolving body of work encompasses linguistics, anthropology, literary and cultural theory, psychoanalysis and postmodern philosophy.